Human security in Turkey : challenges for the 21st century - Özerdem, Alpaslan; Ozerdem, Fusun (Routledge Studies in Security and Conflict Management., 2013)
This edited volume explores human security challenges in the context of Turkey. Turkey occupies a critical geopolitical position between Europe, the Middle East and the Caucasus. It is an important peace-broker in regional conflicts and a leading country in peacekeeping operations, and has been a generous donor for disaster response around the world. However, Turkey is also facing a number of fundamental sociocultural and development challenges and its internal stability is affected by a protracted armed conflict based on Kurdish separatism. In other words, Turkey is at a crossroads.